Carbon ion radiotherapy in the management of non‐small cell lung cancer. Issue Volume 6:Issues 1(2022) (22nd March 2022) - Seneviratne, Danushka; Ishikawa, Hitoshi; Mao, Jingfang; Dougherty, Jingjing M.; Bush, Aaron; Thomas, Mathew; Manochakian, Rami; Lou, Yanyan; Owen, Dawn; Sio, Terence T.; Kirwan, Jessica; Ko, Stephen J.; et al.
Abstract: Despite advancements in local‐regional and systemic therapies, non‐small cell cancer (NSCLC) remains a leading cause of death worldwide. Among those treated with standard‐of‐care modalities, 30–60% experience disease recurrence. Carbon ion radiotherapy (CIRT) is a form of densely ionizing radiotherapy with unique physical and biological advantages over traditional photon and proton modalities. CIRT is expected to have a superior biological impact on tumors, and is believed to be less impacted by the presence of tumor hypoxia or cell cycle state. It also shows highly conformal physical dose deposition due to reduced lateral scattering of the particles, limiting the radiation dose delivered to adjacent organs at risk. To implement CIRT as a viable option in the treatment of NSCLC, technical aspects of treatment delivery – including appropriate beam arrangements, dose calculation algorithms, radiobiological models, and methods of motion management – must be thoroughly investigated. Furthermore, randomized clinical trials comparing CIRT versus traditional radiation modalities must be performed to show the benefits and risks associated with this novel treatment modality. This review discusses the rationale for utilizing CIRT in NSCLC, available clinical data to date, and the potential for future investigations that may pave the path for improving outcomes in those diagnosed with NSCLC. Abstract : Carbon ion radiotherapy is a form of high‐linear energy transfer radiation therapy that may have several theoretical advantages over traditional low‐linear energy transfer therapies in the treatment of both early‐stage and locally advanced non‐small cell cancer. These potential advantages include the ability to achieve high intratumoral radiation doses while sparing adjacent critical structures of the mediastinum, delivering adequate radiation doses in fewer fractions, limiting/eliminating the use of concurrent cytotoxic chemotherapy, and increasing the response to immunotherapy, thereby reducing eventual metastatic spread.